Genetic recombination and diversity of sapovirus in pediatric patients with acute gastroenteritis in Thailand, 2010-2018 - Kattareeya Kumthip (2020)
© 2020 Kumthip et al. Background. Human sapovirus (SaV) is an etiologic agent of acute gastroenteritis (AGE) in all age groups worldwide. Genetic recombination of SaV has been reported from many countries. So far, none of SaV recombinant strain has been reported from Thailand. This study examined the genetic recombination and genotype diversity of SaV in children hospitalized with AGE in Chiang Mai, Thailand. Methods. Stool samples were collected from children suffering from diarrhea who admitted to the hospitals in Chiang Mai, Thailand between 2010 and 2018. SaV was detected by RT-PCR and the polymerase and capsid gene sequences were analysed. Results. From a total of 3,057 samples tested, 50 (1.6%) were positive for SaV. Among positive samples, SaV genotype GI.1 was the most predominant genotype (40%; 20/50), followed by GII.1 and GII.5 (each of 16%; 8/50), GI.2 (14%; 7/50), GIV.1 (4%; 2/50), and GI.5 (2%; 1/50). In addition, 4 SaV recombinant strains of GII.1/GII.4 were identified in this study (8%; 4/50). Conclusions. The data revealed the genetic diversity of SaV circulating in children with AGE in Chiang Mai, Thailand during 2010 to 2018 and the intragenogroup SaV recombinant strains were reported for the first time in Thailand.